Dopaminergic Receptor Type 1 Antagonists and its Possible Role as Preventive Treatment of Post-Traumatic Stress Disorder: A Short Review - Thiago C. Moulin (Journal of Applied Pharmaceutical Science, 2016)
Posttraumatic stress disorder (PTSD) is an overreaction to aversive memories and can cause severe health issue. The prevention or treatment memory of PTSD through pharmacological approaches is a rising field, but still with inconclusive results. In this study, the literatures of dopaminergic D1 antagonist were reviewed and author propose that it can be applied to achieve this goal, mainly due to effects on memory persistence. Moreover, administration of D1 antagonists would be simple with few side effects, making this treatment reasonably practical for human use.
Keywords: PTSD, D1 antagonists, memory persistence.